2011
DOI: 10.1007/s11746-011-1824-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oil Extraction Methods on Physical and Chemical Properties of Red Salmon Oils (Oncorhynchus nerka)

Abstract: The following four methods were used to extract salmon oil from red salmon heads: RS1 involved a mixture of ground red salmon heads and water, no heat treatment, and centrifugation; RS2 involved ground red salmon heads (no water added), heat treatment, and centrifugation; RS3 involved a mixture of ground red salmon heads and water, heat treatment, and centrifugation; and RS4 involved ground red salmon heads, enzymatic hydrolysis, enzyme inactivation by heat and centrifugation. The four extracted oil samples we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Since PV is limited to the initial stages of oxidation, the difference in PVs became significant at the end of the storage period (Jeon & Shahidi, 2002;Rezaei et al, 2008;Woyewoda, Shaw, Ke, & Burns, 1986). We find that PV of extracted oil is in the range those reported by others (Faraji-dana & Gharehkhani, 2016;Norziah, Nuraini, & Lee, 2009;Yin, Solval, Huang, Bechtel, & Sathivel, 2011). In this study, it has been shown that PV immediately exceeded over 10 meq O 2 /kg in oil extracted from trout waste during the first 3 hr.…”
Section: Peroxide Value and Thiobarbituric Acid Testsupporting
confidence: 82%
“…Since PV is limited to the initial stages of oxidation, the difference in PVs became significant at the end of the storage period (Jeon & Shahidi, 2002;Rezaei et al, 2008;Woyewoda, Shaw, Ke, & Burns, 1986). We find that PV of extracted oil is in the range those reported by others (Faraji-dana & Gharehkhani, 2016;Norziah, Nuraini, & Lee, 2009;Yin, Solval, Huang, Bechtel, & Sathivel, 2011). In this study, it has been shown that PV immediately exceeded over 10 meq O 2 /kg in oil extracted from trout waste during the first 3 hr.…”
Section: Peroxide Value and Thiobarbituric Acid Testsupporting
confidence: 82%
“…The high temperature extraction-induced lipid oxidation that determined a variation of the extracted oil color [ 53 , 56 , 57 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Regardless of the method used, minerals were found in all the extracted oil samples. Their concentration depended on the oil‐extraction method, but the most abundant were Ca, Fe, K, Mg, P, and Na . Among these minerals, iron is an effective catalyst of the lipid oxidation.…”
Section: Resultsmentioning
confidence: 99%